2005
DOI: 10.1111/j.1538-7836.2005.01528.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of microparticles released from coated‐platelets

Abstract: Summary. Dual agonist stimulation of platelets with thrombin and convulxin results in generation of coated-platelets, a sub-population of cells known formerly as COAT-platelets (collagen and thrombin). Coated-platelets retain several procoagulant proteins on their surface and express phosphatidylserine (PS). In this report, we utilize a new methodology to demonstrate that coated-platelets also release microparticles. Platelets were prelabeled with 2.5 lM Bodipy-maleimide and then stimulated with convulxin plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 18 publications
1
72
1
Order By: Relevance
“…It will be interesting to explore whether PMP generated by platelet stimulation with combinations of other agonists express differing capacities for classical complement pathway activation. Expression of procoagulant activity and Factor V on activated platelets, for example, is especially pronounced in subsets of platelets referred to as "coated" platelets, activated by thrombin and collagen or thrombin and A23187 [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to explore whether PMP generated by platelet stimulation with combinations of other agonists express differing capacities for classical complement pathway activation. Expression of procoagulant activity and Factor V on activated platelets, for example, is especially pronounced in subsets of platelets referred to as "coated" platelets, activated by thrombin and collagen or thrombin and A23187 [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…After 6 hours, blood was drawn from the retroorbital plexus, and microparticles in mouse plasma were quantified as described previously. 28 …”
Section: Effect Of Lpsmentioning
confidence: 99%
“…Analyses included calculation of descriptive statistics, independent t tests, bivariate and partial correlations for comparison of continuous variables, and 2 or Fisher exact tests for comparison of categorical variables with significance set at PՅ0.05.…”
Section: Methodsmentioning
confidence: 99%
“…1 The biochemical characteristics of coated platelets include a robust prothrombinase activity, retention of several procoagulant proteins on the cell surface, and release of microparticles. 1,2 The critical nature of coated platelets in hemostasis is revealed by a genetic disorder in dogs, in which deficiency of coated platelets results in spontaneous mucosal bleeding and postsurgical hemorrhage. 3 Previous studies in ischemic stroke indicated that coated platelet levels are elevated in patients with nonlacunar stroke as compared with control subjects, a finding in keeping with the thrombotic nature of these events.…”
mentioning
confidence: 99%